Influence des pratiques agropiscicoles sur la biodiversité des étangs de la Dombes (Ain, France) en vue d'une valorisation de produits du terroir - Dominique Vallod; Alexander Wezel (VertigO)
This research project dealt with the influence of pond fisheries and agricultural practices on biodiversity and valorization of local products in the Dombes region in France. This region is a cultural landscape characterised by about 1100 ponds (about 11 000 ha) located in an agricultural area with pastures, cropped fields and forests. A first, ecological objective of this project is to analyze the biodiversity of the ponds within the farming and forestry systems and define a typology of the ponds in considering different species composition in relation to land use around and pond management practices. A second part concerns a socio-economic approach with the analysis of the technical and socio-economic characteristics of farms and the study of local stakeholders and their implication in conservation and management of the pond biodiversity. The first results show that this very complex system presents a significant diversity in terms of macrophytes, dragonflies and amphibians due to the high potential of food in the ponds related to high water nutrient content. The traditional practices have created this biodiversity and are needed to maintain it.